In motion: a transport interchange in Rosebank - Hattingh, Jan Harm (My University, 2010)
This thesis developed from an interest in pedestrian infrastructure and motorised transport. No investigation into the current situation is needed to establish the fact that these two entities struggle to find a balance in the urban and suburban landscape. What does however need investigation is the small pockets throughout the landscape that achieve a balance. R R osebank was chosen as it appears to be one of those pockets where a balance is achieved. However, with the introduction of a major Gautrain underground train station with Oxford Road being streamlined above it and an expected 100 000 daily commuters, the balance will be disturbed. The current station proposal turns its back on the pedestrian realm and promotes motorised transport with little understanding of how such a station can have a positive impact on the urban landscape. This thesis attempts to explore the Gautrain train station as more than just a single idea. Through local investigation it concludes that all forms of transport must be considered when implementing new forms of public transport. An equitable balance must be achieved throughout the entire project. It further explores and implements the theory of linking spaces and commuters throughout the project. It considers various forms of how this can be achieved and finally how visual linkage can be used to guide commuters through what can be a disorienting experience. A large amount of time was spent on site to test theories, gain an understanding of pedestrian and motorist’s needs and to fully understand the potential dynamics of how a transport interchange would affect the existing urban fabric. The project is a transport interchange using the Gautrain station as the nucleus for the platforms, station buildings, new taxi rank, new private taxi pick up point and BRT stations